Voluntary associations and development: The Indian experience - Chakrabarty, Bidyut (2004)
The growing importance of voluntary Organisations is both an outcome and a challenge to what is construed as development in today's parlance. This article makes an effort to understand the phenomenon of voluntarism and underlines conceptualisations suggesting a different, if not an alternative, path of development. An attempt has also been made to identify the distinctive features and role of voluntarism in development in contrast with state-led development in India. The role of voluntary agencies in development was recognised by the Planning Commission since its inception. The article discusses how this role was further strengthened and highlighted in various Five Year Plans. - Reproduced.
Keywords: Nongovernmental organizations - India; Nongovernmental organizations